Central Neurocytoma: Determining Rate of Shunting and Results after Subtotal and Total Excision - Fahmida Arab Mallah, Sardar, Badar Uddin Ujjan, Syed Aamir Shah, Muhammad Mujahid Sharif, Muzamil Dilber, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the shunting rate and the results of control measures in patients having central neurocytoma who underwent total and subtotal resection. Study design: A cross-sectional study Place and Duration This study was conducted in People's University of Medical and Health Sciences for Women Nawabshah from Septmeber 2016 to Septmber 2020 . Methodology: In this study, overall 15 patients were included. Every patient had a follow-up of 2 years. The age of participants was between 13 to 49 years. The data of every patient was recorded which included the demographics (age, gender), early mortality and morbidity, presentation of clinical factors, and radiological findings. The radiological findings include features, tumor location, hydrocephalus, recurrence, and residual. A transcortical approach was used for the treatment of individuals for both, total or subtotal excision. EVD (External Ventricular Drain) was installed which was later replaced by a shunt. For confirmation of diagnosis and guidance of the follow-up, the MIV index and histopathology were used. For residual tumor and recurrence, radiosurgery of Gamma knife or adjuvant radiotherapy was used. Results: There were 3 patients who died due to sepsis and thalamic infarction after the total and subtotal excision. There were 9 patients who had a total excision and 6 patients who had a subtotal excision. Among the 9 patients with a total excision, 3 of them showed small recurrence at 1 year and 18 months follow-up along with a high MIB index. A total of 2 of them needed a shunt. In the remaining participants,the shunt was not placed. Among the 6 patients who had a subtotal excision, 2 of these patients had an early shunt insertion. Five patients were controlled by radiotherapy while one was controlled by radiosurgery. One patient, who was controlled by radiotherapy, failed radiotherapy in his second treatment at 18 months of follow-up. Practical implication : total excision has better results for central neurocytoma and should be considered procedure of choice Conclusion: Central neurocytoma may have a better chance of recovery than other intraventricular tumors if treated with total excision, with a lower incidence of shunt insertion throughout its course. Keywords: neurocytoma, shunt insertion, excision, radiotherapy, total excision